Formulation and evaluation of organo-mineral fertilizers based on sewage sludge optimized for maize and sunflower crops. (December 2021) - Kominko, Halyna; Gorazda, Katarzyna; Wzorek, Zbigniew
Graphical abstract: Highlights: Sewage sludge can be used as substitute for conventional fertilizer resources; Organo-mineral fertilizers optimized for maize and sunflower crops were produced; The share of waste materials in organo-mineral fertilizers was 49–54%; Fertilizer production based on waste allows for organic matter and nutrient recycling. Abstract: The depletion of natural resources, energy consumption and environmental issues relating to fertilizer production processes are driving a move towards a more sustainable use of resources and the recycling of nutrients. With regard to the fertilizer industry, this gives the opportunity to use the fertilizing potential of alternative raw materials. This paper evaluates the possibility of using dried sewage sludge in the manufacture of organo-mineral fertilizers. Fertilizers based on sewage sludge with an addition of poultry litter ash and mineral fertilizers were developed and characterized in the study. It was possible to produce multicomponent organo-mineral fertilizers with optimized compositions for maize and sunflower crops, characterized by total nutrient content over 20%. Moreover, they contained beneficial secondary nutrients and micronutrients originated from waste materials. The fertilizers were free of pathogens and fulfilled the requirements related to heavy metal content according to Polish legislation. The method of manufacturing organo-mineral fertilizers based on waste materials is a simple waste management solution offering organic matter and nutrient recycling in line with the circular economy and reducing reliance on imported raw materials.